Bovine Tuberculosis in European Bison as Possible Zoonotic Impact in Poland - Jerzy, Kita; Krzysztof, Anusz; Andrzej, Salwa; Mirosław, Welz; Blanka, Orłowska; Magdalena, Zaleska (IntechOpen, 2012)
None